An Investigation of RSN Frequency Spectra Using Ultra-Fast Generalized Inverse Imaging - Boyacioglu, Rasim; Beckmann, Christian F.; Barth, Markus (Frontiers in Human Neuroscience, 2013)
With the advancements in MRI hardware, pulse sequences and reconstruction techniques, many low TR sequences are becoming more and more popular within the fMRI community. In this study, we have investigated the spectral characteristics of resting state networks (RSNs) with a newly introduced ultra fast fMRI technique, called Generalized Inverse Imaging (GIN). The high temporal resolution of GIN (TR=50 ms) enables to sample cardiac signals without aliasing into a separate frequency band from the BOLD fluctuations. Respiration related signal changes are, on the other hand, removed from the data without the need for external physiological recordings. We have observed that the variance over the subjects is higher than the variance over RSNs.